2018
DOI: 10.1002/ecs2.2310
|View full text |Cite
|
Sign up to set email alerts
|

Deceptive ecological status of urban streams and rivers—evidence from diatom indices

Abstract: Urbanization directly affects the ecological status of streams and rivers: Their beds and drainage basins are often heavily transformed and their habitat conditions disturbed. The aim of the study was to evaluate the extent of human impact in streams in the city of Łódź, Central Poland (~700,000 inhabitants), by pattern recognition analysis of benthic diatom assemblage samples using a Kohonen artificial neural network, principal component analysis, and indicator species analysis. The study also determined the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 45 publications
0
17
0
Order By: Relevance
“…Planothidium frequentissimum is an eurytopic species that occurs globally in a variety of habitat types, from natural springs to rivers in urban areas with high levels of pollution. Its value as an indicator is low, as confirmed by the Shade Plot analysis, which found it to significantly affect the degree of similarity observed between samples from different environments (Siver et al, 2005; Levkov et al, 2007; Żelazna-Wieczorek, 2011; Kulikovskiy, Lange-Bertalot & Kuznetsova, 2015; Szczepocka, Nowicka-Krawczyk & Kruk, 2018).…”
Section: Discussionmentioning
confidence: 96%
“…Planothidium frequentissimum is an eurytopic species that occurs globally in a variety of habitat types, from natural springs to rivers in urban areas with high levels of pollution. Its value as an indicator is low, as confirmed by the Shade Plot analysis, which found it to significantly affect the degree of similarity observed between samples from different environments (Siver et al, 2005; Levkov et al, 2007; Żelazna-Wieczorek, 2011; Kulikovskiy, Lange-Bertalot & Kuznetsova, 2015; Szczepocka, Nowicka-Krawczyk & Kruk, 2018).…”
Section: Discussionmentioning
confidence: 96%
“…Planothidium frequentissimum is an eurytopic species that occurs globally in a variety of habitat types, from natural springs to rivers in urban areas with high levels of pollution. Its value as an indicator is low, as confirmed by the Shade Plot analysis, which found it to significantly affect the degree of similarity observed between samples from different environments (Siver, et al 2005;Levkov et al 2007;Żelazna-Wieczorek 2011;Kulikovskiy, Lange-Bertalot & Kuznestova 2015;Szczepocka, Nowicka-Krawczyk & Kruk 2018). Recently P. frequentissimum was divided into several different species.…”
Section: Planothidium Frequentissimum (Plfq) (Figs 5 Aa-ff)mentioning
confidence: 95%
“…The structure of algae assemblages and their autecology have been studied, and algae community indices have been developed and used worldwide (Prygiel & Coste, 2000; Kalyoncu, Çiçek, Akköz, & Yorulmaz, 2009; Rakowska & Szczepocka, 2011; Tan, Sheldon, Bunn, & Zhang, 2013; Xia, Zhang, Zhao, & Bunn, 2014; Hassan & Shaawiat, 2015; Szczepocka, Nowicka‐Krawczyk, & Kruk, 2018; Tokatli, Solak, Yilmaz, Arici, & Doyioğlu, 2020). Watanabe's Index (WAT) (Watanabe, Asai, & Houki, 1986) was originally developed in Japan to assess organic pollution in aquatic ecosystems (Watanabe et al, 1986).…”
Section: Introductionmentioning
confidence: 99%
“…The diatom‐based eutrophication/pollution index (EPI‐D) has been reported to be sensitive to Cl − and nutrients (Dell'Uomo, 1996; Prygiel & Coste, 2000). The Biological Diatom Index (IBD) (Prygiel & Coste, 2000) has been widely applied in Europe (Prygiel & Coste, 2000; Kalyoncu et al, 2009; Rakowska & Szczepocka, 2011; Szczepocka et al, 2018; Tokatli et al, 2020) and has been found suitable for evaluating the trophic status and ionic content in water quality assessments in subtropical rivers (Yangtze River basin) in China (Tan et al, 2013). The Pampean Diatom Index (IDP) was developed and used for assessment of rivers and streams in Argentina (Gómez & Licursi, 2001).…”
Section: Introductionmentioning
confidence: 99%